SEISMIC RATE CHANGES ANALYSIS BASED ON THE SPASIAL DISTRIBUTION SEISMOTECTONICS IN THE SOUTHERN SUMATRA REGION - Florentina Simalango, Nora; Syafriani, Syafriani; Dwiridal, Letmi; Zulhendra, Zulhendra (Prodi Fisika FST UNJA, 2024)
The southern Sumatra region experiences high seismic activity, often resulting in large earthquakes that cause significant losses. Before such earthquakes, a phenomenon known as seismic quiescence a decrease in seismic activity commonly occurs. This phenomenon can be analyzed through changes in seismic rates using the spatial distribution of Z-values. This study investigates the occurrence of seismic quiescence before major earthquakes and examines changes in seismic rates in southern Sumatra. Used secondary earthquake data from the United States Geological Survey (USGS) for 1973–2023 were analyzed, focusing on the region between 2.050°S–5.885°S and 101.030°E–106.611°E. The study centered on three significant earthquakes: the 2000 (7.9 Mw), 2001 (7.4 Mw), and 2007 (8.4 Mw) events. Seismic rate changes were analyzed using the Z-value method, dividing the region into grids to calculate and spatially distribute Z-values. Results showed seismic quiescence before the 2000 (±16 years), 2001 (±13 years), and 2007 (±17 years) earthquakes in Bengkulu. Additionally, similar phenomena were observed in Bengkulu and Lampung before 2023, suggesting the potential for future significant earthquakes in the region. These findings highlight seismic quiescence as a precursor to major seismic events.